2019
DOI: 10.3319/tao.2018.09.26.01
|View full text |Cite
|
Sign up to set email alerts
|

Attribution of the growth of a distinct population of Synechococcus to the coverage of lateral water on an upwelling

Abstract: Upwelling water generally transports abundant nutrients to fertilize the euphotic zone and promotes larger phytoplankton to thrive. In contrast, knowledge about the composition of prokaryotic picoplankton associated with the scale of upwelling is limited. In this study, the population compositions of prokaryotic picoplankton, with particular focus on Synechococcus, under two diverse hydrographic conditions in the shelf-margin upwelling system were compared in detail. During the study period of 2009, an upwelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…In the context of global climate change, the accelerated warming might subsequently change the flow direction and velocity of the WBC, thereby affecting the ecology and the biogeochemistry cycle of the surrounding waters (Wu, Wang, Lin, Chiang, & Wu, ; Wu et al, ; Yang et al, ). Picoplankton is highly susceptible to the environmental changes and in turn alters their community compositions or nutrition strategy to respond (Chung & Gong, ; Worden et al, ). Our study provides the first insight into the community assemblage and the annual distribution of picoeukaryotes in the subtropical Kuroshio Current.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of global climate change, the accelerated warming might subsequently change the flow direction and velocity of the WBC, thereby affecting the ecology and the biogeochemistry cycle of the surrounding waters (Wu, Wang, Lin, Chiang, & Wu, ; Wu et al, ; Yang et al, ). Picoplankton is highly susceptible to the environmental changes and in turn alters their community compositions or nutrition strategy to respond (Chung & Gong, ; Worden et al, ). Our study provides the first insight into the community assemblage and the annual distribution of picoeukaryotes in the subtropical Kuroshio Current.…”
Section: Discussionmentioning
confidence: 99%
“…The heterotrophic bacteria were stained with the nucleic acidspecific dye SYBR R Green I (emission = 530 ± 30 nm) in a 10 4 -fold-diluted commercial solution (Molecular Probes, Eugene, OR, United States; Liu et al, 2002). Known numbers of fluorescent beads (TruCOUNT Tubes, Becton-Dickinson, Franklin Lakes, NJ, United States) were simultaneously used as an instrument internal standard (Chung and Gong, 2019;Chan et al, 2020). When applicable, cell abundances were converted to carbon units using the factors widely applied, including 53 fg C cell −1 for Prochlorococcus, 250 fg C cell −1 for Synechococcus, 2100 fg C cell −1 for picoeukaryotes, and 20 fg C cell −1 for heterotrophic bacteria (Lee and Fuhrman, 1987;Morel et al, 1993;Campbell et al, 1994;Buck et al, 1996).…”
Section: Biological Variables and Data Analysesmentioning
confidence: 99%
“…Picoplankton is highly susceptible to environmental changes, including altering its community compositions and/or nutrition strategy to respond (Worden et al, 2015;Chung and Gong, 2019). In addition to increasing nutrient concentrations and phytoplankton biomass, the relative abundances and composition of picophytoplankton also changed due to the coastal uplift.…”
Section: Implication Of the Coastal Uplift Effect On The Kuroshio Eco...mentioning
confidence: 99%
“…In this study, we focused on a more southern Kuroshio current, characterized by low available nutrients in situ. Therefore, the differences found in the abundance of Synechococcus compared with the ndings of Chung and Gong (2019) [58] could be attributed to variations in the formation of upwelling caused by the main or branch currents of the Kuroshio current system. Additionally, this study revealed the presence of Synechococcus in clade VII, clade III, and clade X.…”
Section: Discussionmentioning
confidence: 99%